Outdoor thermal performance simulation in campus area during the dry season, Yogyakarta - Hasti Widyasamratri; Arif Kusumawanto; Fadhilla Tri Nugrahaini (Universitas Islam Sultan Agung, 2019)
The outdoor thermal performance reflects the microclimate condition in any significant area. This study simulated the thermal performance with measured and modeled three meteorological parameters, air temperature (Ta), relative humidity (RH), and wind speed in the dry season tropical city. The research focused on thermal performance simulation and distribution, here, we were neglecting anthropogenic activities as the heat source. The result showed that there were different ranges between a measured and simulated value of Ta, RH, and wind speed. The highest Ta difference between measure and simulation occurred at 11 AM, which was 1.97⸰C. The highest difference of RH occurred at 13 PM (26.75%), and the highest different of wind speed was at 11 AM (0.37 m/s) respectively. The heat distribution in the focus area was influenced by the solar direction which impacted the ground and near-surface air temperature.